Halogen Bonding I Impact on Materials Chemistry and Life Sciences - Metrangolo, Pierangelo; Resnati, Giuseppe (Topics in Current Chemistry, 2015)
The nature and directionality of halogen bonding; the sigma hole, by Timothy Clark, Peter Politzer, Jane S. Murray Solid-state NMR study of halogen-bonded adducts, by David Bryce Infrared and Raman measurements of halogen bonding in cryogenic solutions, by Wouter Herrebout Halogen bonding in the gas phase, by Anthony C. Legon Halogen bonding in solution, Mate Erdelyi Unconventional motifs for halogen bonding, by Kari Rissanen Halogen bonding in supramolecular synthesis, Christer Aakeröy Halogen bond in synthetic organic chemistry, Stefan M. Huber Anion recognition in solution via halogen bonding, Mark S. Taylor Anion transport with halogen bonds, by Stefan Matile Halogen bonding in silico drug design, by Pavel Hobza, Kevin Riley Biological halogen bonds: An old dog with new tricks, by P. Shing Ho Principles and applications of halogen bonding in medicinal chemistry, by Frank M. Boeckler Halogen bond in molecular conductors and magnets, by Marc Foumigué Halogen bonding towards design of organic phosphors, by Wei Jun Jin Halogen bond in photoresponsive materials, by Pierangelo Metrangolo, Giuseppe Resnati, Arri Priimagi.